Comparative Pharmacokinetics of Three Bioactive Diterpenoids of Rabdosia serra Extract in Normal and Con A-Induced Liver Injury Rats Using UPLC-MS/MS - Liu, Fangle; Zeng, Yun; Dai, Pengyu; Huang, Kaiwen; Zhang, Kaihui; Tao, Tao; Wang, Meiqi; Zhu, Chenchen; Lin, Chaozhan (Frontiers in Pharmacology, 2022)
Rabdosia serra (R. serra), one of the source plants of “Xihuangcao”, has been widely used as a Chinese folk herb with the concomitant function of both medicine and foodstuff for the prevention and treatment of liver disease. Diterpenoids were considered as the major bioactive components in R. serra responsible for their effect on hepatoprotection in previous phytochemical and pharmacological studies, while few comparative pharmacokinetic studies have been conducted under the physiological and pathological conditions. To reveal the difference in the pharmacokinetics process of R. serra extract (RSE) in normal and Con A-induced liver injury rats, a rapid UPLC-MS/MS method (total running time: 5 min) was established to simultaneously determine three bioactive diterpenoids (enmein, epinodosin, and isodocarpin) in rat plasma. The results showed significant differences in pharmacokinetic properties of three analytes between physiological and pathological states. Compared with normal rats, the AUC of three analytes was remarkably higher in liver injury rats, while the Tmax, T1/2, and MRT were shortened. It indicated that RSE has higher exposure and quicker elimination in liver injury rats than that in normal rats. Our results suggested that the pharmacokinetics of hepatoprotective medications was affected by liver injury, which prospected to provide essential information for guiding the healthcare and clinical application of R. serra in pathological states.